Single-Cell Analysis of Target Antigens of CAR-T Reveals a Potential Landscape of “On-Target, Off-Tumor Toxicity” - Zhang, Yinyin; Li, Yingmei; Cao, Weijie; Wang, Fang; Xie, Xinsheng; Li, Yadan; Wang, Xiaoyi; Guo, Rong; Jiang, Zhongxing; Guo, Rongqun (Frontiers in Immunology, 2021)
Cellular immunotherapy represented by CD19-directed chimeric antigen receptor T (CAR-T) cell has achieved great success in recent years. More and more CAR-T therapies are being developed for cancer treatment, but the frequent and varied adverse events, such as “on-target, off-tumor toxicity”, limit the CAR-T application. Here, we identify the target antigen expression patterns of CAR therapies in 16 tissues and organs (peripheral blood mononuclear cell, bone marrow, lymph node, spleen, heart, ascending aortic tissue, trachea, lung, skin, esophagus, stomach, small intestine, rectum, liver, common bile duct, and pancreas) from healthy human at scRNA-seq levels. The atlas determines target antigens expressed on some normal cell types, which facilitates to elucidate the cause of “on-target, off-tumor toxicity” in special tissues and/or organs by targeting some antigens, but others not. Moreover, we emphatically describe the target antigen expression patterns of B-lineage-derived malignant cells, AML, and solid tumors. Overall, the present study indicates the pathogenesis of “on-target, off-tumor toxicity” during CAR therapies and provide guidance on taking corresponding preventive measures during CAR treatment.